1972
DOI: 10.1136/hrt.34.3.244
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory and circulatory effects of pentazocine. Review of analgesics used after myocardial infarction.

Abstract: and the Royal Infirmary, SheffieldThe analgesic pentazocine has been studied in myocardial infarction. A dose of 30 mg given intravenously provokes significant respiratory depression (which may be potentiated by lignocaine). This dose caused a small, but not significant rise in systemic arterial pressure and heart rate when breathing air. Attempts to provoke postural hypotension failed. Changes in pulmonary arterial pressure and arteriovenous oxygen difference were small and not significant.The published repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1975
1975
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Many reports suggested that pentazocine shows cardioprotective effects in human in the early phase after cardiac surgery or isolated ischemic heart (3,21,27,33). However, it is unclear whether chronic pentazocine treatment inhibits heart failure following PO-induced hypertrophy.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Many reports suggested that pentazocine shows cardioprotective effects in human in the early phase after cardiac surgery or isolated ischemic heart (3,21,27,33). However, it is unclear whether chronic pentazocine treatment inhibits heart failure following PO-induced hypertrophy.…”
Section: Discussionmentioning
confidence: 98%
“…The ameliorated effect of pentazocine after cardiac ischemia is reported in the Langendorff-perfused isolated heart preparation (27). Moreover, pentazocine shows cardioprotective effects in human or rodents after cardiac surgery (3,14,21,33). Although the previous studies suggested that pentazocine regulates Ca 2ϩ mobilization from sarcoplasmic reticulum (SR)/endoplasmic reticulum (ER) through opioid or -1 receptors ( 1 R) (8, 23), the precise cardioprotective mechanisms of pentazocine in cardiomyocytes remain unclear.…”
mentioning
confidence: 99%
“…In high doses seizures may occur (Challoner et al, 1990). Respiratory depression is weaker than with morphine and is subject to a 'ceiling' effect (Nagle and Pilcher, 1972). Respiratory depression is weaker than with morphine and is subject to a 'ceiling' effect (Nagle and Pilcher, 1972).…”
Section: Dosages and Routes Of Administrationmentioning
confidence: 99%
“…Mean arterial pressure showed a slight increase in women after epidural administration of meperidine (Khaw et al, 2000). Pethidine and pentazocine increase the heart rate and systemic arterial pressure after its use in myocardial infarction in man (Lee et al, 1976;Nagle and Pilcher, 1972). This increase in systemic arterial pressure was assumed to be caused by peripheral resistance.…”
Section: Haemodynamic Changes [(Systolic Arterial Pressure (Sap)/diasmentioning
confidence: 99%